PENGGUNAAN SIMULASI LIVEWIRE UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATA KULIAH SISTEM PERALATAN ELEKTRONIK - Rahmi, Aidhia (Jurnal EDik Informatika, 2020)
This study aims to determine the effect of the use of livewire simulations on electronic equipment system pre-laboratory, on the subject of the running LED character to improve students understanding of concepts. The research design used was one group pretest posttest design. The population of this research is students physics education at STKIP PGRI West Sumatra. As for the sample research is all students who take electronic equipment system courses. The results showed that the simulation of livewire can be increased students' understanding of the concept seen from the average pretest and posttest scores as well as the normalized gain value obtained, which is <g> = 0.425 in the medium category.